Presence of Inulin-Type Fructo-Oligosaccharides and Shift from Raffinose Family Oligosaccharide to Fructan Metabolism in Leaves of Boxtree (Buxus sempervirens) - Van den Ende, Wim; Coopman, Marlies; Vergauwen, Rudy; Van Laere, André (Frontiers in Plant Science, 2016)
from raffinose family oligosaccharide to fructan metabolism in leaves of boxtree (Buxus sempervirens) Wim Van den Ende1,* Marlies Coopman1, Rudy Vergauwen1, André Van Laere1 1 KU Leuven, Laboratory of Molecular Plant Biology, Institute of Botany and Microbiology, Kasteelpark Arenberg 31, B-3001 Leuven, Belgium * Correspondence: Wim Van den Ende, Laboratory of Molecular Plant Biology, Institute of Botany and Microbiology, Kasteelpark Arenberg 31, B-3001 Leuven, Belgium tel +32 16321952; fax +32 16321967; Wim.vandenende@bio.kuleuven.be Keywords: inulin, oligosaccharides, stress, RFO, fructan Abstract Fructans are known to occur in 15% of flowering plants and their accumulation is often associated with stress responses. Typically, particular fructan types occur within particular plant families. The family of the Buxaceae, harbouring Pachysandra terminalis, an accumulator of graminan- and levan-type fructans, also harbours boxtree (Buxus sempervirens), a cold and drought tolerant species. Surprisingly, boxtree leaves do not accumulate the expected graminan- and levan-type fructans but small inulin fructo-oligosaccharides (FOS: 1-kestotriose and nystose) and raffinose family oligosaccharides (RFO: raffinose and stachyose) instead. The seasonal variation in concentrations of glucose, fructose, sucrose, FOS and RFO were followed. Raffinose and stachyose peaked during the winter months, while FOS peaked at a very narrow time-interval in spring, immediately preceded by a prominent sucrose accumulation. Sucrose may function as a reserve carbohydrate in winter and early spring leaves. The switch from RFO to fructan metabolism in spring strongly suggests that fructan and RFO fulfil distinct roles in boxtree leaves. RFO may play a key role in the cold acclimation of winter leaves while temporal fructan biosynthesis in spring might increase sink strength to sustain the formation of new shoots.